Pengaruh Brand Image dan Kualitas Produk terhadap Keputusan Pembelian Fore Coffee: The Influence of Brand Image and Product Quality on Fore Coffee Purchase Decision - Wulandari, Listya; Hastasari, Ratih; Setiawan, Wawan (CV Warnak Johanna Nusantara, 2026)
The growth of local coffee shops like Fore Coffee reflects the rapid development of the coffee industry in Indonesia. Fore Coffee has successfully built an image as a premium coffee brand through the use of digital technology, contemporary concepts, and effective branding strategies. This study aims to determine and analyze the influence of brand image and product quality on the purchasing decisions of Fore Coffee consumers, both partially and simultaneously. The research uses a quantitative approach with a questionnaire method, where data is collected through the distribution of questionnaires to 96 respondents who are Fore Coffee consumers. The research results show that partially, brand image has a significant effect on purchasing decisions with a t-value of 6.846 ≥ t-table 1.986 and significance 0.000 ≤ 0.05. Similarly, product quality also has a significant effect with a t-value of 10.226 ≥ t-table 1.986 and significance 0.000 ≤ 0.05. Simultaneously, brand image and product quality have a significant effect on purchasing decisions with an f-value of 58.191 ≥ f-table 3.093 and significance 0.000 ≤ 0.05. These findings affirm that a strong brand perception and maintained product quality play a crucial role in shaping consumer purchasing decisions.